Cardioprotective Effects of Grapefruit IntegroPectin Extracted via Hydrodynamic Cavitation from By-Products of Citrus Fruits Industry: Role of Mitochondrial Potassium Channels - Lorenzo Flori; Lorenzo Albanese; Vincenzo Calderone; Francesco Meneguzzo; Mario Pagliaro; Rosaria Ciriminna; Federica Zabini; Lara Testai (Foods, 2022)
Citrus flavonoids are well-known for their beneficial effects at the cardiovascular and cardio-metabolic level, but often the encouraging in vitro results are not confirmed by in vivo approaches; in addition, the clinical trials are also inconsistent. Their limited bioavailability can be, at least in part, the reason for these discrepancies. Therefore, many efforts have been made towards the improvement of their bioavailability. Hydrodynamic cavitation methods were successfully applied to the extraction of byproducts of the Citrus fruits industry, showing high process yields and affording stable phytocomplexes, known as IntegroPectin, endowed with great amounts of bioactive compounds and high water solubility. The cardioprotective effects of grapefruit IntegroPectin were evaluated by an ex vivo ischemia/reperfusion protocol. Further pharmacological characterization was carried out to assess the involvement of mitochondrial potassium channels. Grapefruit IntegroPectin, where naringin represented 98% of the flavonoids, showed anti-ischemic cardioprotective activity, which was better than pure naringenin (the bioactive aglycone of naringin). On cardiac-isolated mitochondria, this extract confirmed that naringenin/naringin were involved in the activation of mitochondrial potassium channels. The hydrodynamic cavitation-based extraction confirmed a valuable opportunity for the exploitation of Citrus fruits waste, with the end product presenting high levels of Citrus flavonoids and improved bioaccessibility that enhances its nutraceutical and economic value.